Counseling on Giving Turmeric Simplisia Tea Drinks to Breastfeeding Mothers in Telaga Sari Village, Tanjung Morawa District, Deli Serdang Regency - Erlina Nasution; Ardiana Batubara; Fitriyani Pulungan (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
Exclusive breastfeeding plays a very important role in reducing child morbidity and mortality, because breast milk is the best food that contains the nutrients that are needed by babies at the age of 0-6 months. milk production. The goal in community service is for breastfeeding mothers to know and understand the benefits of giving turmeric simplicia tea which can increase milk production. The method used is lectures, questions and answers/discussions and giving simple turmeric tea to nursing mothers. The target in this community service is all breastfeeding mothers in Telaga Sari Village, Tanjung Morawa District, Deli Serdang Regency, a total of 40 people. 15 respondents (37.5%) have sufficient and insufficient knowledge and 10 respondents (25%) have good knowledge. Whereas after counseling about the benefits of turmeric simplicia tea on increasing milk production in breastfeeding mothers there was an increase where respondents who had good knowledge were 30 people (75%), respondents who had sufficient knowledge were 8 people (20%) and respondents who had good knowledge less than 2 people (5%). It can be concluded that counseling can change the knowledge of breastfeeding mothers about the benefits of turmeric simplia tea which is very effective in increasing breast milk production in nursing mothers